Design of novel microstrip patch antenna for millimeter-wave B5G communications - Tiang, Jun Jiat; Alsekait, Deema Mohammed; Khan, Imran; Wang, Pi-Chung; Madsen, Dag Øivind (Frontiers in Materials, 2024)
The simplicity of integration and co-type features of microstrip antennas make them intriguing for a broad variety of applications, particularly with the growing usage of mmWave bands in wireless communications and the constant rise in data transfer in communication situations. This paper proposes a novel design of micrstrip patch antenna for mmWave B5G communication. The main idea is to realize four-mode antenna the operates in four different frequencies. The geometry is rectangular patch whose resonance frequency is adjusted by varying the walls and pins of the structure. Simulation results show that the proposed antenna design has improved fractional bandwidth and performance as compared with existing antennas. The observed curve indicates that, in agreement with the modeling findings, there are four resonance spots in the operational frequency region of 2.5 to 3.4 GHz: 2.68 GHz, 2.9 GHz, 3.05 GHz, and 3.3 GHz, which correspond to TM1/2,0, TM3/2,0, and TMRS, respectively, and TM1/2,2 four resonant modes, within the frequency range, the observed antenna gain peak is around 9 dBi, which is consistent with the measured results.